2015
DOI: 10.1371/journal.pone.0133713
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Core of the Myostatin Prodomain: Its Interaction with Both Type I and II Membrane Receptors, and Potential to Treat Muscle Atrophy

Abstract: Myostatin, a muscle-specific transforming growth factor-β (TGF-β), negatively regulates skeletal muscle mass. The N-terminal prodomain of myostatin noncovalently binds to and suppresses the C-terminal mature domain (ligand) as an inactive circulating complex. However, which region of the myostatin prodomain is required to inhibit the biological activity of myostatin has remained unknown. We identified a 29-amino acid region that inhibited myostatin-induced transcriptional activity by 79% compared with the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 35 publications
7
33
1
Order By: Relevance
“…The result of Jiang et al[16] in which a GST-fused human MSTNpro consisting of residues 42–98 showed no MSTN-inhibitory capacity supports the mechanism, as well as our current result. On the other hand, it has been reported that synthetic MSTNpro peptides containing residues in the N-terminal fragment (below Arg-98) of BMP-1-digested MSTNpro have MSTN-inhibitory capacity in vitro [1719], as well as enhancement of muscle growth upon administration of the peptides[17, 18]. The apparent contradictory results can be related to the administration dose of peptides.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The result of Jiang et al[16] in which a GST-fused human MSTNpro consisting of residues 42–98 showed no MSTN-inhibitory capacity supports the mechanism, as well as our current result. On the other hand, it has been reported that synthetic MSTNpro peptides containing residues in the N-terminal fragment (below Arg-98) of BMP-1-digested MSTNpro have MSTN-inhibitory capacity in vitro [1719], as well as enhancement of muscle growth upon administration of the peptides[17, 18]. The apparent contradictory results can be related to the administration dose of peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, the MSTN-binding affinity of the BMP-1-digested N-terminal fragment of MSTNpro appears to be very weak, it is thus speculated that C-terminal region from the BMP-1-digested point stabilizes the binding to MSTN. In support of this speculation, the MSTNpro peptides containing residues in the BMP-1-digested N-terminal fragment required micromolar concentration to suppress MSTN activity [1719]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] It is important to note that all strategies to inhibit myostatin are not equal in their action. [17] Moreover,i no ur synthetic peptide-based study, amouse-derived peptide consisting of 23 aa residues (position: 21-43, peptide A; Scheme 1) showed effective inhibitory activity against myostatin, while ah uman-derived peptides equence did not. To the best of authors' knowledge,n os mall peptides inhibiting myostatin have been describedt od ate in the literature.…”
mentioning
confidence: 99%
“…[2,14] In the structural study of inactivated TGF-b1, the N-terminal a-helical region of the prodomain,w hich is conserved among superfamily proteins, interacts with the type Ir eceptor binding site of mature TGF-b1. [17] Moreover,i no ur synthetic peptide-based study, amouse-derived peptide consisting of 23 aa residues (position: 21-43, peptide A; Scheme 1) showed effective inhibitory activity against myostatin, while ah uman-derived peptides equence did not. [16] In recent investigations on the key peptide sequence responsible for myostatin inhibition from the same prodomain, using as eries of fusion proteins with the antibody Fc fragment, Ohsawa et al successfully found as horter 29 aa residue fragment located at positions 19-47.…”
mentioning
confidence: 99%